Coverage of the Brazilian population 18 years and older by private health plans: an analysis of data from the World Health Survey Cobertura da população brasileira com 18 anos ou mais por plano de saúde privado: uma análise dos dados da Pesquisa Mundial de Saúde - Francisco Viacava; Paulo Roberto Borges de Souza-Júnior; Célia Landmann Szwarcwald (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
This study analyzes data from the World Health Survey (WHS) conducted in 2003, with a sample of 5,000 individuals 18 years and older. Some 24.0% of the interviewees had private health insurance, and the main variables associated with private coverage were number of household assets, age, level of education, formal employment, living in municipalities with more than 50,000 inhabitants, and good self-rated health. The socioeconomic profiles of needs for and use of health services in the population covered by private health plans are different, confirming the findings of other studies reporting that this population segment as a whole presents better health conditions and greater use of services as compared to the population without private coverage, even after adjusting for socio-demographic variables and self-rated health. The WHS data also suggest that individuals with private health plans do not always use their insurance to pay for services, except in the case of mammograms. Esse estudo analisa os dados da Pesquisa Mundial de Saúde (PMS), realizada em 2003, em uma amostra de 5 mil indivíduos com 18 anos ou mais. Cerca de 24,0% dos indivíduos entrevistados têm seguro privado de saúde, sendo que os fatores associados à posse do plano são o número de bens, idade, escolaridade, ter emprego formal, residir em municípios com menos de 50 mil habitantes e referir boa auto-avaliação do estado de saúde. Os perfis sócio-demográficos de necessidades e uso de serviços de saúde da população coberta por plano de saúde são distintos, confirmando os achados de outros trabalhos que referem que esse segmento populacional como um todo apresenta melhores condições de saúde e um maior uso de serviços em relação à população não coberta por seguro de saúde, mesmo após o controle por variáveis sócio-demográficas e a auto-avaliação do estado de saúde. Os dados da PMS também sugerem que pessoas cobertas por plano de saúde nem sempre utilizam o plano para pagamento de serviços, excetuando-se o caso da mamografia.